A META-ANALYSIS OF THE EFFECT OF DISCOVERY LEARNING MODEL ON STUDENTS' CONCEPTUAL UNDERSTANDING AND MATHEMATICAL REASONING ABILITIES - Khairunnisa, Khairunnisa (International Journal of Education, 2025)
The existence of inconsistencies in the results of primary research on the effectiveness of the Discovery Learning model on students' ability to understand concepts and mathematical reasoning encouraged researchers to conduct research that aims to examine the differences in the effect of the discovery learning model on students' ability to understand concepts and mathematical reasoning as a whole as well as in terms of educational level, sample size, and research demographics. This test was conducted using a Systematic Literature Review (SLR) with a meta-analysis method to obtain more comprehensive conclusions. Through testing on 41 primary studies, it was found that the implementation of the Discovery Learning model had a significant effect on the mathematical concepts understanding abilities as a whole. The study characteristics of the educational levels and research demographics lead to differences in the effect of the students' mathematical concept understanding abilities, with the highest effect at the junior high school education level and the demography of the research islands of Bali and Nusa Tenggara. However, the study characteristics of the sample size did not show any differences in the effect. In addition, it was also found that the implementation of the Discovery Learning model had a significant effect on the mathematical reasoning abilities as a whole after testing 45 primary studies. The study characteristics of the sample size led to differences in the effect of the students' mathematical reasoning abilities, with the highest effect on a sample size of less than 30 students. However, the study characteristics of educational levels and research demographics did not show any differences in the effect. Thus, the results of this study imply that educators can implement the Discovery Learning model as an effort to improve students' mathematical conceptual understanding and reasoning abilities.